A Cross-Sectional Study to Assess the Physical and Psychological Well-Being among Older Adults during COVID-19 Outbreak - Kanishkar, S.; Saravanan, S.; Tamizharasi, K. (International Journal of Nursing Research, 2023)
Background: The pandemic caused by the COVID-19 virus is an international health crisis that has the potential to have major repercussions for public health, including both physical and mental health. There is a lack of epidemiological information about the COVID-19 outbreak, which makes elderly people more susceptible to the stress it causes. The goal of the study is to evaluate older persons’ physical and mental health during the COVID-19 pandemic. Methods: Mixed method, embedded design was adopted. Fifty older adults were selected through purposive sampling technique from the selected village. Qualitative approach was used to measure physical well-being by interview and quantitative approach was employed to assess psychological well-being by modified psychological general well-being index. Qualitative data analyzed by thematic analysis and quantitative data analyzed by descriptive and inferential statistics. Results: The study findings revealed that, in physical well-being, maximum older adults reported, the daily schedule was totally changed, did not get enough time for doing pleasurable activities, changed their food pattern, sleep was fully disturbed, daily habits were changed by following COVID appropriate behavior, and many discomfort faced in maintaining health during COVID-19 outbreak. The finding of psychological well-being shows, maximum 34 (68%) having moderate level of psychological distress, the domain self-confidence 3.1 ± 30.68 was mostly disturbed. There was a significant association found between the age, education, occupation, performance of basic activity, and vaccination status with the selected demographic variables at P ≤ 0.05 levels. Conclusion: The older adults were considered as vulnerable people as they need more attention in maintaining health during COVID-19 outbreak